Sleep quality and awareness of factors affecting insomnia among people over the age of 20 - Wiącek, Aleksandra (Journal of Education, Health and Sport, 2018)
Introduction: The problem of insomnia affects many of us, but most of us are unaware of what factors affect the quality of our sleep. Insomnia is insufficient length, or unsatisfactory quality of sleep. Health consequences of insomnia may be m.in .: problems in daily functioning manifested by difficulties in remembering, impaired concentration, reduced immunity, which increases the possibility of multiple somatic diseases.Objective of the work: The aim of the study was to assess the prevalence of insomnia and its determinants in a selected group of people over the age of 20.Material and methods : The research was covered by 119 people from different social groups over the age of 20 years old. The study was made by using a diagnostic survey of the author's questionnaire. Used for statistical analysis chi-kwardat Pearson. Results and conclusions: The analysis of the data shows that people surveyed insomnia is a very common phenomenon. Unfortunately, factors affecting Insomnie are not underestimated by. Both individuals living in rural 65.55% and urban 34.45% suffer from sleep disorders. As many as 39.50% of respondents confirmed the difficulty in falling asleep, which are among the factors insomnia.